The Problem of the Validity of Verified Electronic Signatures on Party Deeds and the Challenges for the Performance of Land Deed Officials - Herman, Jesselyn Valerie; Phortolomeius, Michelle Florentin (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The emergence of cyber notary in Indonesia reflects an urgent response to society’s growing demand for fast, secure, and accessible legal services. Within civil law, authentic deeds (akta autentik) created by notaries hold the highest evidentiary value, as regulated under Articles 1866–1868 of the Civil Code. One of the essential elements ensuring the authenticity of such deeds is the signature of both parties and the notary. The development of information technology has introduced electronic signatures as a legal alternative to handwritten signatures, recognized under the Electronic Information and Transactions Law (UU ITE). However, a normative conflict arises since Article 5(4) UU ITE excludes notarial deeds from electronic documents, while the Notary Law (UUJN) still requires physical signatures and presence. This regulatory disharmony has caused electronic-signed notarial deeds to risk being downgraded from authentic deeds to private deeds, reducing their evidentiary weight in civil procedure. The implications are significant: not only is legal certainty weakened, but notaries also face greater liability if disputes occur. Through a normative juridical approach, this study highlights the need for legal reform that explicitly accommodates cyber notary practices and electronic signatures, ensuring that digital transformation does not undermine the legal certainty and evidentiary strength of authentic deeds.